Differential Search Optimized Random Forest Regression Algorithm for State of Charge Estimation in Electric Vehicle Batteries - Hossain Lipu M.S.; Hannan M.A.; Hussain A.; Ansari S.; Ayob A.; Saad M.H.M.; Muttaqi K.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Battery management systems; Charging (batteries); Data handling; Decision trees; Digital storage; Electric vehicles; Learning algorithms; Lithium-ion batteries; Machine learning; Differential search algorithm; Electric vehicle batteries; Lithium ions; Lithiumion battery; Random forest regression; Random forests; Regression algorithms; Search Algorithms; State-of-charge estimation; States of charges; Regression analysis